The Existence Of The International Anarcho-Syndicalism Movement Based On Indonesian Law Perspective - Ledy Nelsih Rumala; Jeffry A. Ch. Likadja; Viktor Eben Sabuna (Catuspata, 2023)
Anarcho-syndicalism is an ideology in which workers want to work freely, not bound by rules. Anarcho-syndicalism is an ideology that wants the dissolution of all political power institutions that are narrated to oppress and exploit workers to be replaced by free communities bound by socio-economic interests. This research aims to find out the existence of the anarcho-syndicalist movement based on international law and the readiness of national law in facing the threat of anarcho-syndicalist ideology in Indonesia. The research method used in this research is normative legal research (library research) which has relevance to the research issues studied. Sources and legal materials used are primary, secondary, and tertiary legal materials. Based on the results of the research that has been carried out, it is known that the existence of the anarcho-syndicalism movement in terms of International Law has an impact on the application of the Right to freedom of association for workers/laborers as regulated in ILO (International Labour Organization) Convention No. 87 of 1948 concerning freedom of association and protection of the right to organize. Furthermore, the State has regulated people who join organizations to commit criminal offenses or prohibited organizations will be subject to imprisonment or fines, namely by what is written in the Criminal Code/KUHP (Kitab Undang-Undang Hukum Pidana) Article 261 concerning Participation in Organisations to commit Criminal Offences.